Inhibiting methanogenesis by targeting thermodynamics and enzymatic reactions in mixed cultures of rumen microbes in vitro - Tanaka, Kairi; Collins, Scott; Polkoff, Kathryn; Fellner, Vivek (Frontiers in Microbiology, 2024)
Inhibiting methane (CH4) represents an opportunity to improve the sustainability, productivity, and profitability of ruminants. Ruminal methanogenesis can be mitigated via two primary strategies: (1) alternative electron acceptors and (2) enzymatic inhibition. The former utilizes thermodynamic favorability of reactions like nitrate/nitrite reduction to ammonia (NH3) while the latter targets specific enzymes using structural analogues of CH4 such as bromochloromethane (BCM). In this study, we investigated the effects of four additives and their combinations on CH4 concentration in mixed cultures of rumen microbes. Sodium nitrate (NaNO3), sodium sulfate (Na2SO4), and 3-nitro-1-propionate (3NPA) were included as thermodynamic inhibitors, and BCM was included as a kinetic inhibitor. The effect of additives included at three levels was evaluated in Experiment 1 and 2. The highest level of each additive was used to determine the combined effect of NaNO3 + Na2SO4 (NS), NS + 3NPA (NSP), and NSP + BCM (NSPB) in Experiments 3 and 4. Basal diets consisted of alfalfa hay and a concentrate mix formulated to obtain three forage to concentrate ratios: 70:30 (HF), 50:50 (MF), and 30:70 (LF), respectively. Experimental treatments were placed in culture bottles and incubated at 39°C for 6, 12, or 24h. Measurements included CH4, H2, pH, NH3-N, and short chain fatty acids, as well as amplicon sequencing using two (universal and archaea-specific) primer sets for the 16S rRNA V4-V5 regions and another for the fungal ITS2 region. Addition of NaNO3 decreased (p<0.001) CH4 and butyrate and increased (p<0.03 and 0.005, respectively) acetate and propionate. Cultures receiving NaNO3 had an enrichment of microorganisms capable of nitrate and nitrite reduction. Na2SO4 did not decrease (p>0.10) CH4. 3NPA inhibited CH4 but to a lesser extent. Irrespective of level of inclusion, BCM inhibited (p<0.001) methanogenesis, decreased (p<0.002) total short chain fatty acids (SCFA) and acetate and increased (p<0.001) H2 and propionate. The relative abundance of Methanobrevibacter was decreased in the presence of BCM, both alone and in the NSPB treatment. Here, we provide a proof of concept that the combination of an electron acceptor and a methane analogue may be exploited to improve microbial efficiency via methanogenesis inhibition.